The Prevalence and Significance of Jejunal and Duodenal Bulb Polyposis After Duodenectomy in Familial Adenomatous Polyposis: Retrospective Cohort Study. Issue 6 (December 2021) - Yoon, Ji Yoon; Mehta, Neal; Burke, Carol A.; Augustin, Toms; O'Malley, Margaret; LaGuardia, Lisa; Cruise, Michael; Mankaney, Gautam; Church, James; Kalady, Matthew; Walsh, R. Matthew; Bhatt, Amit
Abstract : Objective: To evaluate the prevalence, natural history, and severity of polyposis of the duodenal bulb and jejunum after duodenectomy in patients with FAP. Summary of Background Data: Advanced duodenal polyposis stage in FAP requires consideration of duodenal resection to prevent cancer; pylorus-preserving approach of pancreas-sparing duodenectomy (PSD) is preferred. Post-duodenectomy data indicate polyps occur in the duodenal bulb and the post-anastomotic jejunum, but limited data exists regarding their significance. Methods: We identified consecutive FAP patients After duodenal resection, including pancreaticoduodenectomy, PSD, or segmental duodenectomy, at Cleveland Clinic. Medical records were used to determine time to diagnosis of duodenal bulb or jejunal polyps, length of follow up, and severity of polyposis including maximal Spigelman stage (SS) of jejunal polyposis (neo-SS). Results: 64 patients with FAP underwent duodenectomy and endoscopic follow up. 28% underwent pancreaticoduodenectomy, 61% PSD, and 11% segmental duodenectomy. Postoperatively, 38/64 (59%) were diagnosed with jejunal polyposis, with median time to diagnosis of 55 months and follow up time of 127 months. Jejunal polyposis was advanced in 21% (neo- SS III or IV). Fifty percent were treated endoscopically, 1 patient required surgery. Jejunal polyp-free survival after duodenectomy differed by surgery type ( P = 0.008). A total of 55/64 patients underwent a pylorus-preserving procedure, and 6/55 (11%) developed duodenal bulb polyps. All bulb polyps were large (>20 mm) and found after PSD. Endoscopic resection was unsuccessful in 5 patients, but no surgical intervention was required. Conclusions: Polyposis occurs in the remaining duodenal and jejunal mucosa in the majority of patients after surgical duodenectomy. Jejunal polyposis is advanced in 1 in 5 patients, but rarely requires surgery. Endoscopic management of jejunal polyposis seems feasible but has proven difficult for duodenal bulb polyps. Abstract : Supplemental Digital Content is available in the text